Sight Threatening Diabetic Retinopathy in Type ? 2 Diabetes Mellitus - Khalid I. Talpur, Mohammad Memon, Sajjad Ali Surhio , Shahzad Memon, Noor Bakht Nizamani (Pakistan Journal of Ophthalmology, 2014)
Purpose: To determine the proportions of Proliferative Diabetic Retinopathy (PDR) and Clinically Significant Macular Edema (CSME) in patients with known type–2 Diabetes Mellitus. Material and Methods: A prospective study was conducted at Ophthalmology Department, Liaquat University of Medical and Health Sciences, Hyderabad, Pakistan. Duration of study was one year, starting from 1st January 2010 till 31st December 2010. Two hundred consecutive type – 2 diabetics diagnosed with diabetic retinopathy were classified according to the most severe changes in the worse eye into the following three stages based on EDTRS classification. 1) Patients with Non–Proliferative Diabetic Retinopathy (NPDR). 2) Patients with CSME stage (in the presence of NPDR). 3) Patients with PDR stage (irrespective of presence or absence of CSME). Results: The mean age of patients with diabetic retinopathy was 51.7 ± 9.4 years. 62 (31%) patients had PDR, and another 66 (33%) patients had CSME. 51.6% of patients with PDR were in the age group of 40 – 49 years and 56% of patients with CSME were 50 – 59 years. Patients presented with PDR were significantly younger (P–value < 0.001) than patients with CSME and NPDR. 51% of patients had DM for 15.7 ± 6.1 years; with a mean age of 30.5 ± 4.6 years at diagnosis with type – 2 DM. Conclusion: 64% of patients had sight – threatening stages of diabetic retinopathy, and 34.4% of them were 40 – 49 years of age.